Routine use of bilateral internal thoracic artery grafting in women does not increase in-hospital mortality and could improve long-term survival. (1st September 2018) - Gatti, Giuseppe; Castaldi, Gianluca; Morra, Laura; Forti, Gabriella; Benussi, Bernardo; Sinagra, Gianfranco; Pappalardo, Aniello
Abstract: Background: Bilateral internal thoracic artery (BITA) grafting is underused in women. Methods: Outcomes of 798 consecutive women with multivessel coronary disease who underwent isolated coronary surgery (1999–2016) using BITA ( n  = 530, 66.4%) or single internal thoracic artery (SITA) grafting ( n  = 268, 33.6%) were reviewed retrospectively. Differences between BITA and SITA cohort were adjusted by propensity score matching. For both series, late survival was estimated with the Kaplan-Meier method. Results: One-to-one propensity score matching resulted in 247 BITA/SITA pairs with similar baseline characteristics and risk profile. According to the propensity matching, BITA grafting was associated with a trend towards reduced in-hospital mortality (3.2% vs. 5.7%, p  = 0.19). However, BITA women had an increased chest tube output ( p  = 0.0076) as well as higher rates of any (13% vs. 5.3%, p  = 0.003) and deep sternal wound infections (9.3% vs. 4.9%, p  = 0.054), this translating in a longer in-hospital stay (10 vs. 9 days, p  = 0.029). Test for interaction showed that body mass index > 30 kg/m 2 and extracardiac arteriopathy were associated with a higher risk of deep sternal wound infection in BITA than in SITA women (23.4% vs. 13.7%, p  < 0.001 and 23.9% vs. 3.4%, p  = 0.001, respectively). Freedom from all-cause death and cardiac or cerebrovascular death were improved in BITA cohort, even though the differences were not quite significant ( p  = 0.16 and 0.076, respectively). Conclusions: When routinely performed, BITA grafting does not increase in-hospital mortality in women and could improve long-term survival. However, its use should be avoided in obese women with extracardiac arteriopathy because of increased risk of deep sternal wound infection.